SINTESIS KOMPOSIT SELULOSA-POLIPROPILENA DENGAN REAGEN FENTON SEBAGAI AGEN PENGKOPLING - Simpen, I Nengah; Sutha Negara, I Made (Jurnal Kimia (Journal of Chemistry); Vol. 7, No. 1 Januari 2013, 2013)
The research was conducted to observe of mixture ratio of cellulose from eceng gondok, concentrations of H 2 O 2 /Fe 2+ (Fenton reagent), and concentrations of polypropylene from plastic garbage wich produced optimum condition to composite production with strong mechanics and biodegradable properties. This research was conducted by determination of optimum condition in composite forming of cellulose-PP. Steps performed within forming of cellulose-PP were (1) purification of plastic garbage to get polypropylene (PP); (2) cellulose extraction of from enceng gondok by alkaline extraction; continued with (3) composite forming of cellulose-PP through reaction of free radical with Fenton reagent as insiator. Determination of optimum conditions for the formation of cellulose-PP composite was conducted by varying some variables influencing the properties of mechanicals and biodegradability of cellulose-PP composite that is concentration ratio between cellulose and PP and concentration of H 2 O 2 . Composite of cellulosa-PP to be tested by mechanicals properties (elasticity modulus (MOE), breaking modulus (MOR), and density and also its ability of water absorption test and biodegradability test on dry land and wet land. The result gave optimum ratio of 1:3 and optimum concentration of H 2 O 2 of 0.5%. Analysis of Laser Induced Breakdown Spectroscopy (LIBS) showed that the hardness of EG-PP was higner than with plastic PP and that insertion of cellulose molecule in composite was successful. Its optimum conditionthe EG-PP composite can adsorp 18.73% water and biodegradable properties.
Keywords: composite, eceng gondok, plastic garbage, cellulose, Fenton reagent